Reaction of 2-Hetaryl-2-(tetrahydro-2-furanyliden)acetonitriles with 1,3-N,N-Binucleophiles - Milokhov, Demyd S.; Khilya, Olga V.; Volovenko, Yulian M.; Palamarchuk, Gennady V.; Shishkin, Oleg V. (Synlett, 2012)
The reactions of 2-hetaryl-2-(tetrahydro-2-furanyliden)acetonitriles with 1,3-N,N-binucleophiles have been investigated. The mechanisms of the reactions have been discussed. Domino reactions of 2-hetaryl-2-(tetrahydro-2-furanyliden)acetonitriles with amidines can provide an efficient access to 3-[2-substituted 6-amino-5-hetaryl-4-pyrimidinyl]-1-propanols.
Keywords: Michael addition; 2-hetaryl-2-(tetrahydro-2-furanyliden)acetonitriles; binucleophiles; amidines; ring-transformation reactions; ω-hydroxyalkyl heterocycles; pyrimidines